Bioethanol Production from Spirulina (Arthrospira platensis) by Microwave-Assisted Acid Hydrolysis Pretreatment - Ma'mun, Sholeh; Prasetio, Muhammad Wisnu; Anugrah, Aditya Rizki (Universitas Negeri Semarang, 2024)
The world's high consumption of fossil energy increases carbon dioxide (CO2) emissions. The depletion of fossil fuel sources, combined with rising CO2 emissions, has prompted intensive research into renewable energy sources. Bioethanol is an environmentally friendly energy source that has the potential to reduce reliance on gasoline. Bioethanol is produced through the fermentation of monosaccharides. The first and second generations of bioethanol are derived, respectively, from food crops, agricultural waste, and plantations, while the third generation is derived from algae. However, the third generation bioethanol research is still being conducted intensively to develop an optimal process. Macro/microalgae are low-level plants that have the potential to become raw materials for bioethanol. Arthrospira platensis, a spirulina species, is a microalgae with a high carbohydrate content. Apart from that, this type of microalgae is easy to cultivate and grow. This research aims to determine the reducing sugar content which are monosaccharides produced from acid hydrolysis using a microwave at a temperature of 100 °C for 60 – 120 minutes with 0.2 M H2SO4 as the solvent. The hydrolysate obtained was then fermented anaerobically with Saccharomyces cerevisiae in a shaking water bath. The High Performance Liquid Chromatography (HPLC) test was carried out to identify the reducing sugar groups in the hydrolysate. Moreover, the solid content of the biochar remaining from the hydrolysis process was analyzed using Fourier-Transform Infrared Spectrometer (FTIR). From the test results, it was found that the highest concentration of D-glucose (1.19 g/L) occurred at 90 minutes of the hydrolysis. In addition, the hydrolysis of microalgae was also carried out with 0.3 M H2SO4 solvent for 90 minutes. The hydrolysate was then fermented for 96 hours. From the distillation process, it was obtained a bioethanol yield of 2.89%.